Pendidikan Calon Imam di Flores dalam Paradigma Misi Inter Gentes - Monteiro, Yohanes Hans; Jewadut, Jean Loustar; Manuk, Martinus Burong; Nirmala, Fransiska Rosari (Institut Filsafat dan Teknologi Kreatif Ledalero, 2024)
This article focuses attention on the educational praxis of prospective priests in Flores within the inter gentes mission paradigm. The education of prospective priests in the Catholic Church in Flores is still a closed education, namely an educational process that separates people from society for a form of life that is separate from society. Educational praxis like this can be fruitful output who considers himself a 'master' with all-round qualities for all pastoral matters. On this basis, it is very important to create a inter gentes mission paradigm as a theological basis for the practical education of prospective priests in Flores. Gentes in understanding inter gentes understood as nations, cultures, and groups of people with distinctive views and lifestyles. Mission inter gentes considered suitable to answer the needs of Flores which is marked by cultural diversity and a society that still faces the problem of poverty. The education of priest candidates in Flores is carried out in the inter gentes mission paradigm requires the educational practice of prospective priests to be more open to the complexity of the reality of life which is marked by the plurality of religions, cultures and perspectives in society. Apart from that, the commitment to defending the environment and involving women in the formation of prospective priests is also a concern of the mission inter gentes.Keywords: Education; Candidate for Priest; Church; Inter Gentes Mission